2017
DOI: 10.1016/j.bone.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Utility of quantitative micro-computed tomographic analysis in zebrafish to define gene function during skeletogenesis

Abstract: The zebrafish is a powerful experimental model to investigate the genetic and morphologic basis of vertebrate development. Analysis of skeletogenesis in this fish is challenging as a result of the small size of the developing and adult zebrafish. Many of the bones of small fishes such as the zerbafish and medaka are quite thin, precluding many standard assays of bone quality and morphometrics commonly used on bones of larger animals. Microcomputed tomography (microCT) is a common imaging technique used for det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…The three‐dimensional (3D)‐high‐resolution micro‐computed tomography has become established as a powerful method to assess bone morphology and microstructure in zebrafish . Using a 5 μm voxel size, bone structure indices as vertebral bone volume, thickness, and eccentricity can be characterized .…”
Section: Phenotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…The three‐dimensional (3D)‐high‐resolution micro‐computed tomography has become established as a powerful method to assess bone morphology and microstructure in zebrafish . Using a 5 μm voxel size, bone structure indices as vertebral bone volume, thickness, and eccentricity can be characterized .…”
Section: Phenotypingmentioning
confidence: 99%
“…Using a 5 μm voxel size, bone structure indices as vertebral bone volume, thickness, and eccentricity can be characterized . Neural arch area, which reflects modeling arising from osteoblast and osteoclast activity, can also be captured . Because of their small size, whole body, high‐resolution scans are readily acquired .…”
Section: Phenotypingmentioning
confidence: 99%
“…We complemented this functional analysis with ex-vivo µ-CT imaging to examine the morphology of the adult zebrafish heart in fine detail. With a few exceptions (Descamps et al, 2014;Vagberg et al, 2015;Babaei et al, 2016;Weinhardt et al, 2018;Ding et al, 2019), this technique has been mainly used for ex-vivo samples focusing on the skeleton (Charles et al, 2017;Hur et al, 2017;Silvent et al, 2017;C. J. Watson et al, 2020).…”
Section: Optimization Of Preclinical Cardiac Imaging Analysismentioning
confidence: 99%
“…BMP1 is a secreted enzyme that functions in the cleavage of C-propeptides from procollagen precursors (28). We and others previously showed that zebrafish germline loss-of-function mutants for plod2 and bmp1a exhibit severe skeletal abnormalities as adults, reminiscent of OI phenotypes (1,27,29,30).…”
Section: Somatic Mutants For Plod2 and Bmp1a Exhibit Differences In Vmentioning
confidence: 99%